Modeling of Grid Tied PV Inverter to Improve its Performance During Unbalanced Load and Unbalance Fault - Khanal, Bibek; Bhattarai, Kulchandra; Shrestha, Lenish; Dahal, Aashish; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2024)
Integrating solar through inverter brings about various challenges in the microgrids and the inverter itself. This paper aims to the study of problems in the operation of inverter during unbalance load and unbalance fault condition along with the possible control measures to mitigate those problems to ensure the safe and reliable operation of the inverter. A grid connected PV inverter is modeled using hysteresis band controller and implementing the MPPT of the PV system with the buck boost converter. During unbalance load and unbalance fault condition, the negative and zero sequence components of current exists. All the zero-sequence component of current is delivered by the grid. The negative sequence component of current also flows through the inverter resulting in high value of current and loss of stability. Also, the voltage across the dc link capacitor increases during fault. The high value of current flowing through the inverter and high voltage across dc link capacitor may damages the inverter and capacitor respectively. An inverter dual current controller is introduced replacing the hysteresis band control such that the negative sequence component of current flowing through the inverter is almost mitigated from 600A to 10A and positive sequence current is also reduced relatively to a tolerable value 150A from 550A. The total current flowing through the inverter is limited to 200A from 950A and voltage across dc link capacitor is limited to 700V from 1050V during LG fault at the inverter side thus ensuring safe operation of the inverter during voltage dip condition. A further study can be done on limiting the positive sequence component of current to a rated value and improving the performance while operating in islanded mode.